GAMBARAN TINGKAT KEPUASAN PASIEN BPJS RAWAT JALAN TERHADAP PELAYANAN KEFARMASIAN DI INSTALASI FARMASI RSD IDAMAN BANJARBARU TAHUN 2019 - Depy Oktapian Akbar; Gusti Dewi Handayani; Aristha Novyra Putri (Jurnal Ilmiah Ibnu Sina (JIIS): Ilmu Farmasi dan Kesehatan, 2020)
Pharmaceutical services are health services that have an important role in realizing a good quality health. Hospitals as health services must pay attention to the quality of services, especially after the implementation of the national health insurance program (BPJS). The service quality of service can be assessed by description the patient satisfaction level. This study aims to description the patient satisfaction level of BPJS outpatient towards pharmaceutical services in the Idaman Banjarbaru Hospital. This research was a non-experimental research with descriptive research by using cross-sectional approach. The study was conducted at the Pharmacy Installation of Idaman Banjarbaru Hospital in May - June 2019. Samples were selected by purposive sampling on 100 respondents of BPJS outpatients. The research instrument was in a questionnaire form, to measure the five dimensions of patient satisfaction. The description results of the satisfaction level of BPJS outpatients towards pharmaceutical services in the Pharmacy Installation of Idaman Banjarbaru Hospital seen from the 5 dimensions of service that were obtained an average score of reliability at 86.30%, Responsiveness at 84.45%, Assurance at 84.75% , Emphaty at 85.75% and Tangible at 84.70%. The Conclusion is the patient felt very satisfied with the pharmaceutical services at the Pharmacy Installation with an average value of all dimensions at 85.19%.